The Influence of Workload, Work Motivation, and Creativity on Lecturer Performance in the Management Department of UPN Veteran Yogyakarta in the Digital Era - Polonde, Sri Jumiati; Wahyuni, Purbudi; Ambarwati, Sri Dwi Ari (CV. Strata Persada Academia, 2025)
In response to the challenges of digital transformation in higher education, this study examines the influence of workload, work motivation, and creativity on lecturer performance in the Management Department of Universitas Pembangunan Nasional